Nuclear Hormone Receptors in Parasitic Platyhelminths - Wu, Wenjie (Mol Biochem Parasitol, 2019)
Nuclear receptors (NRs) belong to a large protein superfamily which includes intracellular receptors for secreted hydrophobic signal molecules, such as steroid hormones and thyroid hormones. They regulate development and reproduction in metazoans by binding to the promoter region of their target gene to activate or repress mRNA synthesis. Isolation and characterization of NRs in the parasitic trematode Schistosoma mansoni identified two homologues of mammalian thyroid receptor (TR). This was the first known protostome exhibiting TR homologues. Three novel NRs each possess a novel set of two DNA binding domains (DBD) in tandem with a ligand binding domain (LBD) (2DBD-NRs) isolated in Schistosoma mansoni revealed a novel NR modular structure: A/B-DBD-DBD-hinge-LBD. Full length cDNA of several NRs have been isolated and studied in the parasitic trematodes S. mansoni, S. japonicum and in the cestode Echinococcus multilocularis. The genome of the blood flukes S. mansoni, S. japonicum and S. haematobium, the liver fluke Clonorchis sinensis and the cestode Echinococcus multilocularis have been sequenced. Study of the NR complement in parasitic Platyhelminths will help us to understand the role of NRs in regulation of their development and understand the evolution of NR in animals.